Lessons from evaluation of CCAFS outcomes to improve outcome delivery and reporting: Lessons learned from 2016-2019 outcome case evaluations - Szilagyi, Lili; Schuetz, Tonya; Thornton, Philip K.; Dinesh, Dhanush; Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
To help CCAFS projects improve on reporting outcomes, we looked at all project outcome cases that were submitted between 2016 and 2019 and how they were evaluated. The findings of this investigation provide some lessons learned on what helps to make a strong outcome story as well as common mistakes to avoid.